(untitled) (Biological Sciences - PJSIR, 2006)
. Samples of poultry broiler and layer rations (n = 865) were received at Romer Laboratories Pakistan from different parts of the country over a period of 31 months for the purpose of their mycotoxin analysis. The samples were analyzed by thin layer chromatography and by HPLC. The mycotoxins analysed included aflatoxin-B (AfB ), zearalenone 1 1 (Zon), deoxynivalenol (Don), 3-acetyldeoxynivelenol (3ac-Don), 15-acetyldeoxynivelenol (15ac-Don), nivalenol (Niv), fusarenon-x ( Fus-x), T-2 toxin (T-2), HT-2 toxin (Ht-2), diacetoscirpenol (Das), neosolaniol (Neos) and ochratoxin-A 1 (OtA). The mycotoxin AfB was noted to be the major contaminant in the feed samples analyzed (84.70% in 182 1 1 feeds), followed by OtA (51% in 41 feeds), Zon (49.33% in 150 feeds), Don (38% in 150 feeds), T-2 (34.65% in 101 feeds), 3ac-Don (19.41% in 67 feeds), and 15ac-Don (11.94% in 67 feeds). Mean values with standard deviation for AfB , OtA, Zon, Don, T-2 toxin, 3ac-Don and 15ac-Don were 13±16.80 mg/kg, 10±19.63 mg/kg, 213.58±440 mg/kg, 456±1122 mg/kg, 442.56±1191 mg/kg, 41±102 mg/kg, and 38.92±149.58 mg/kg, respectively. All samples were ob- served to be negative for HT-2 toxin, Das, neosolaniol, nivalenol, and fusarenon-x. This study is the first report on the occurrence of a range of mycotoxins in the Pakistani poultry rations, which shows that AfB , OtA, Zon, T-2 toxin, Don, 3ac-Don and 15ac-Don may be present at levels, which adversely affect poultry production.